Manejo gubernamental del territorio oceánico mexicano (1953-2018) - Aguilar Aguilar, Rosenda (Universidad Michoacana de San Nicolás de Hidalgo, 2023)
The oceans, like the rest of the terrestrial systems, are not exempt from the powerful human influence. They have been the object of normative, economic, political, administrative, social, scientific, technological, cultural, and religious decisions that human beings have resolved over time. The purpose of this doctoral research is to examine the government management that Mexico has developed over its oceans, and poses the following research question as its central axis: Has the Mexican government, during the period of 1953-2018, addressed ocean subsistence in the same intensity with which it has carried out economic activities on its ocean territory? The research process is based on the Driver-Pressure-State-Impact-Response model (DPSIR), which establishes as a theoretical premise that each decision has consequences. In this sense, the management of the oceanic system has been analyzed from a causal perspective, studying eight Drivers (fisheries, mariculture, algal extraction, salt extraction, oil extraction, tourism, commercial maritime transport, and submarine fiber optic cabling) and recognizing the Responses of the government ocean support administration (AGSO) in the indicated period. The results confirm the proposed hypothesis: for the period of 1953-2018, the Mexican government has rapidly promoted economic activities on its ocean territory, while those of ocean subsistence have not been a priority. Given this, the research reveals the points of improvement that would be key to establish new responses from the Mexican government or to optimize the current ones.

Los océanos, al igual que el resto de los sistemas terrestres, no están exentos de la poderosa influencia humana. Han sido objeto de las decisiones normativas, económicas, políticas, administrativas, sociales, científicas, tecnológicas, culturales y religiosas, que el ser humano ha resuelto a lo largo del tiempo. La presente investigación doctoral se enfocó en examinar el manejo gubernamental que México ha desarrollado sobre sus océanos, y planteó como eje central la siguiente pregunta de investigación: ¿El gobierno mexicano, durante el periodo de 1953-2018, ha atendido el sostenimiento oceánico en la misma intensidad con que ha llevado a cabo las actividades económicas sobre su territorio oceánico? El proceso de investigación se ha basado en el modelo Fuerza-Presión-Estado-Impacto-Respuesta (FPEIR) (Driver-Pressure-State-Impact-Response, DPSIR), el cual establece como premisa teórica que cada decisión acarrea consecuencias. De esta forma, el manejo del sistema oceánico se ha analizado desde una perspectiva de causalidad estudiando ocho Fuerzas (pesquerías, maricultura, extracción algal, extracción de sal, extracción petrolera, turismo, transporte comercial marítimo y cableado submarino con fibra óptica) y reconociendo las Respuestas de la Administración Gubernamental de Sostenimiento Oceánico (AGSO) en la temporalidad señalada. Los resultados confirman que, para el periodo de 1953-2018, el gobierno mexicano ha fomentado aceleradamente las actividades económicas sobre su territorio oceánico, mientras que las de sostenimiento oceánico no han sido prioritarias. Ante esto, la investigación revela los puntos de mejora que serían clave para establecer nuevas Respuestas del gobierno mexicano u optimizar las actuales.
Facultad de Economía Vasco de Quiroga. Doctorado en Ciencias en Desarrollo Sustentable
Keywords: http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/16371; info:eu-repo/classification/cti/5; FEVAQ-R-D-2023-0647; Sostenimiento oceánico; Administración gubernamental; Metodología PFEIR (DPSIR)